Aromatic Interactions in Organocatalyst Design: Augmenting Selectivity Reversal in Iminium Ion Activation. Issue 28 (15th May 2015) - Holland, Mareike C.; Metternich, Jan Benedikt; Daniliuc, Constantin; Schweizer, W. Bernd; Gilmour, Ryan
Abstract Substituting N‐methylpyrrole for N‐methyindole in secondary‐amine‐catalysed Friedel–Crafts reactions leads to a curious erosion of enantioselectivity. In extreme cases, this substrate dependence can lead to an inversion in the sense of enantioinduction. Indeed, these closely similar transformations require two structurally distinct catalysts to obtain comparable selectivities. Herein a focussed molecular editing study is disclosed to illuminate the structural features responsible for this disparity, and thus identify lead catalyst structures to further exploit this selectivity reversal. Key to effective catalyst re‐engineering was delineating the non‐covalent interactions that manifest themselves in conformation. Herein we disclose preliminary validation that intermolecular aromatic (CH–π and cation–π) interactions between the incipient iminium cation and the indole ring system is key to rationalising selectivity reversal. This is absent in the N‐methylpyrrole alkylation, thus forming the basis of two competing enantio‐induction pathways. A simple L‐valine catalyst has been developed that significantly augments this interaction.